Proceedings 2014 Network and Distributed System Security Symposium 2014
DOI: 10.14722/ndss.2014.23288
|View full text |Cite
|
Sign up to set email alerts
|

The Sniper Attack: Anonymously Deanonymizing and Disabling the Tor Network

Abstract: Abstract-Tor is a distributed onion-routing network used for achieving anonymity and resisting censorship online. Because of Tor's growing popularity, it is attracting increasingly larger threats against which it was not securely designed. In this paper, we present the Sniper Attack, an extremely low cost but highly destructive denial of service attack against Tor that an adversary may use to anonymously disable arbitrary Tor relays. The attack utilizes valid protocol messages to boundlessly consume memory by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…To render target clients to connect to a malicious webserver, thus revealing their IP addresses. Jansen et al [12] found an implementation error in current Tor clients. The proposed sniper attack could also find the sender in an anonymous network by exhausting the target's memory.…”
Section: Related Workmentioning
confidence: 99%
“…To render target clients to connect to a malicious webserver, thus revealing their IP addresses. Jansen et al [12] found an implementation error in current Tor clients. The proposed sniper attack could also find the sender in an anonymous network by exhausting the target's memory.…”
Section: Related Workmentioning
confidence: 99%
“…Rob Jansen, Florian Tschorsch from US Naval Research Laboratory and Aaron Johnson from Humboldt University of Berlin proposed a new denial of service attack method for Tor network, called Sniper attack [8]. The method can destroy any node of Tor.…”
Section: Active Attackmentioning
confidence: 99%
“…We did not attempt to investigate how guard sets would cope under DoS attacks such as the Sniper Attack [13], where the intent is to simply observe more clients. We expect that guard sets may suffer more than other entry schemes if the attack is to maximize the number clients observed by the adversary.…”
Section: Future Work and Conclusionmentioning
confidence: 99%